The Combined Contribution of Vascular Endothelial Cell Migration and Adhesion to Stent Re-endothelialization - Wang, Xiaoli; Fang, Fei; Ni, Yinghao; Yu, Hongchi; Ma, Jia; Deng, Li; Li, Chunli; Shen, Yang; Liu, Xiaoheng (Frontiers in Cell and Developmental Biology, 2021)
Coronary stent placement inevitably causes mechanical damage to endothelium, leading to endothelial denudation and in-stent restenosis (ISR). Re-endothelialization depends mainly on the migration of vascular endothelial cells (VECs) adjacent to the damaged intima, as well as the mobilization and adhesion of circulating VECs. To evaluate the combined contribution of VEC migration and adhesion to re-endothelialization under flow and the influence of stent, in vitro models were constructed to simulate various endothelial denudation scales (2 mm/5 mm/10 mm) and stent deployment depth (Flat/ Groove/Bulge). Our results showed that: (1) in 2 mm Flat/Groove/Bulge models, VEC migration and adhesion combinedly completed the percent of endothelial recovery about 27%, 16%, 12%, the migration accounted for about 21%, 15%, 7%, respectively. It was suggested that Flat and Groove model was in favor of VEC migration. (2) With augment of the injury scales (5 mm and 10 mm), the contribution of circulating VEC adhesion on endothelial repair increased. Taken together, endothelial restoration mainly depended on the migration of adjacent VECs when injury scale was 2 mm. The adhered cells contributed to re-endothelialization in an injury scale-dependent way. This study is helpful to provide new enlightenment for surface modification of cardiovascular implants.